2021
DOI: 10.1016/j.lanwpc.2021.100131
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of hearing changes in women and men from denarians to nonagenarians

Abstract: Background: Hearing loss needs to be diagnosed and treated early, especially in older individuals, since presbycusis potentially increases the risk of depression and dementia. However, standard data on hearing thresholds across the life-span in Japanese individuals are lacking.Methods: In a retrospective consecutive sample of 10681 native-Japanese speakers (37.3% men; 10-99 years; left-right hearing threshold difference of < 15 dB for all tested pure tones; free of external, middle, or inner ear disease), we d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 32 publications
3
16
0
Order By: Relevance
“…In fact, our data on hearing loss indicated that the deterioration from the previous year was more evident in men. This is consistent with the worsening of the disorder with age in men more than women ( 20 , 21 ).…”
Section: Discussionsupporting
confidence: 86%
“…In fact, our data on hearing loss indicated that the deterioration from the previous year was more evident in men. This is consistent with the worsening of the disorder with age in men more than women ( 20 , 21 ).…”
Section: Discussionsupporting
confidence: 86%
“…11 Wang & Puel noted sharply sloping curve in high frequency in males compared to gradual slope in females. 12 A study by Wasana K et al reported slow age-related decline with an audiogram showing deterioration at 1, 2 and 4 kHz with a typical moderately sloping curve (mechanical cochlear conductive) 13 which was the most predominant curve in this study as well. In a Nigerian study published in 2013, Sogebi OA et al reported a predominance of serial pattern with a flat loss involving both speech and higher frequencies.…”
Section: Discussionsupporting
confidence: 64%
“…In contrast, study by Demeester K et al revealed more hearing loss in females compared to males, with a flat curve of the audiogram, 15 while Wasano K et al did not report any significant gender difference in youngest and oldest age groups. 13 Audiogram findings are critical in predicting inner ear degeneration and hence current study is of significant importance. 17…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study, we built and analyzed the largest database to date of hearing thresholds and other audiometric data of Japanese people aged 10–90 years [ 17 ]. These data were obtained through a retrospective clinical chart cross-sectional study and reported standard age- and gender-specific audiometric data [ 17 ]. To avoid bias from outliers, we excluded data of patients who had hearing thresholds that deviated from the population means.…”
Section: Introductionmentioning
confidence: 99%